Laser-Induced Optical Breakdown in Methane: Diagnostic Using H-Gamma Line Broadening. (9th August 2009) - Parigger, Christian G.; Oks, Eugene
Abstract : Measurements and analysis are reported of Stark-broadened profiles of the H-gamma line emitted from plasma formed by Laser-Induced Optical Breakdown (LIOB) in a pulsed methane flow. Electron densitiesN e are deduced for 18 instants of time in the range between 0.4 and 2.1 microseconds after LIOB and for 2 different gas pressures. The obtained values ofN e are in a good agreement with the corresponding values found previously from Stark-broadened profiles of the H-alpha and H-beta lines.